Unraveling the morphology-structure-property relationship of silver orthovanadate p-semiconductor: experimental and theoretical investigation - Cruvinel, Guilherme Henrique; de Oliveira, Regiane Cristina; de Oliveira, Marisa Carvalho; Pinatti, Ivo Mateus; Ribeiro, Renan Augusto Pontes; Longo, Elson (Universidade Federal de São Carlos, 2024)
Silver vanadate (Ag3VO4) is considered one of the most important semiconductors. It finds practical applications in electrochemical cells, as bactericidal and virucidal agents, in photocatalysis, and environmental remediation. Despite the impressive experimental progress, the dependence of the properties of a material is strongly linked to its chemical composition and structure. In this sense, the peculiar physical-chemical properties of the vanadate's class have become important. However, the fundamentals of structure in this material remain poorly understood, and the theoretical insight into the morphology linked to its properties is completely missing. In the present study, different synthesis times were tested in the obtention of Ag3VO4 crystals by the microwave-assisted hydrothermal method, and their properties were discussed based on experimental results and quantum mechanics simulations. Structural characterizations (XRD, Raman and UV–vis spectroscopy, FE-SEM, and TEM analyses) confirmed the material order at short, medium, and long-range. Theoretical calculations contributed to identifying the atom distribution in the structure, nature of the type of electronic transition, and density of states present in the valence and conduction bands. The topological analysis of the electron density indicated transit chemical interactions and unexpected argentophilic interactions, and Mulliken, Hirshfeld and Bader population analysis provided the charges present on the chemical elements of the crystal. Predicted theoretical surface shapes and their stabilities were evaluated along with FE-SEM images.
Keywords: Semiconductor; Ag3VO4; Microwave-assisted hydrothermal synthesis; DFT simulations; Vanadate; 9. Indústria, Inovação e Infraestrutura